1999
DOI: 10.1111/j.1574-6968.1999.tb13386.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of aromatic compounds by microalgae

Abstract: The microbial degradation of aromatic pollutants has been well characterized over a period of more than 30 years. The microbes of most interest have been bacteria and fungi. Only relatively recently has the question of how algae figure in the catabolism of these compounds attracted a degree of interest. The aim of this review is to highlight the biodegradative capabilities of microalgae on aromatic compounds, ranging from simple monocyclic to more complex polycyclic pollutants. This paper will briefly encompas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(80 citation statements)
references
References 45 publications
0
75
1
4
Order By: Relevance
“…Although bacteria play a key role in the biodegradation of organic pollutant, recent studies indicated that, in addition to providing oxygen for aerobic bacterial biodegradation, microalgae can also biodegrade organic pollutants directly (Semple et al, 1999). It was reported that more than 30 azo compounds were biodegraded and decolorized by Chlorella pyrenoidosa, Chlorella vulgaris and Oscillateria tenuis, in which azo dyes were decomposed into simpler aromatic amine (Liu and Liu, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although bacteria play a key role in the biodegradation of organic pollutant, recent studies indicated that, in addition to providing oxygen for aerobic bacterial biodegradation, microalgae can also biodegrade organic pollutants directly (Semple et al, 1999). It was reported that more than 30 azo compounds were biodegraded and decolorized by Chlorella pyrenoidosa, Chlorella vulgaris and Oscillateria tenuis, in which azo dyes were decomposed into simpler aromatic amine (Liu and Liu, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As primary producer in aquatic ecosystems, microalgae play an important role in generating primary organic substances and it is the base of aquatic food-chain. Algae can interact with aquatic contaminants, which include negative effects on algal growth and function and algal degradation of the contaminants (Semple et al, 1999;Wang et al, 2007;Yang et al, 2002). Algae may also take up aquatic contaminants, thereby acting as a medium for bioconcentration and subsequent biomagnification in higher trophic levels (Sijm et al, 1998;Soares et al, 2008;Vazquez-Duhalt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalene, DDT Biswas et al (2015) Chlorella sp. Naphthalene Semple et al (1999) Dunaliella sp. Mirex Priyadarshani et al bioremediation is an eco-friendly, cost-effective, precisely sensible technique for resolving the environment problems.…”
Section: Resultsmentioning
confidence: 99%
“…However, the conventional techniques are used often, but they can only transform their form; therefore, the next generation water treatment techniques are in high demand. Algal Scenedesmus obliquus DDT, parathion Semple et al (1999) Dunaliella sp., Cylindrotheca sp. Naphthalene, DDT Biswas et al (2015) Chlorella sp.…”
Section: Resultsmentioning
confidence: 99%